2006
DOI: 10.1055/s-2006-944662
|View full text |Cite
|
Sign up to set email alerts
|

The use of self-expanding metal stents to treat acute esophageal variceal bleeding

Abstract: In this pilot study, the new method of implantation of an esophageal stent was found to be a safe and effective treatment for massive bleeding from esophageal varices in patients with liver cirrhosis. These initial clinical results will of course have to be confirmed in comparative studies including a large number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 11 publications
3
117
0
9
Order By: Relevance
“…Recently preliminary studies have shown that the placement of self-expanding metallic stents as an alternative to balloon tamponade for the control of refractory variceal hemorrhage may be beneficial [41,42] but these findings must be confirmed in other trials before their use can be introduced in clinical practice. Emergency EGD may be at the same time diagnostic and therapeutic.…”
Section: Management Of Variceal Bleedingmentioning
confidence: 99%
“…Recently preliminary studies have shown that the placement of self-expanding metallic stents as an alternative to balloon tamponade for the control of refractory variceal hemorrhage may be beneficial [41,42] but these findings must be confirmed in other trials before their use can be introduced in clinical practice. Emergency EGD may be at the same time diagnostic and therapeutic.…”
Section: Management Of Variceal Bleedingmentioning
confidence: 99%
“…The Polyflex stent is being increasingly used for benign esophageal strictures and has also been used with success in the management of post-operative esophageal leak [58] . Another novel use for temporary esophageal stent placement was in the management of acute esophageal variceal bleeding [59] . Although the findings of this small study were positive, a large comparative trial would be required before SEMS could replace the current therapy for bleeding varices.…”
Section: Resultsmentioning
confidence: 99%
“…В ноябре 2002 г. Ян Даниш попытался остановить кровотечение из ВРВ пищевода у 27-летнего мужчины, страдавшего ПГ в исходе хроничес-кого вирусного гепатита С и ВИЧ-инфекции, перенёсшего за 3 года до этого трансплантацию печени, осложнённую тяжёлой коагулопатией, путём имплантации саморасширяющегося ме-таллического стента. Кровотечение было оста-новлено, а стент после стабилизации клиничес-кой ситуации был удалён из пищевода через несколько дней [28,29]. Это послужило началом использования саморасширяющихся металли-ческих стентов, ранее применявшихся при ле-чении злокачественных пищеводных стенозов, перфораций пищевода и трахеопищеводных свищей, для остановки кровотечения из ВРВ пи-щевода у больных ПГ [8, 23,41,43].…”
Section: казанский медицинский журнал 2016 г том 97 №6unclassified